Assessing Planning Ability Across the Adult Life Span in a Large Population-Representative Sample: Reliability Estimates and Normative Data for the Tower of London (TOL-F) Task. (30th January 2019) - Unterrainer, Josef M.; Rahm, Benjamin; Kaller, Christoph P.; Wild, Philipp S.; Münzel, Thomas; Blettner, Maria; Lackner, Karl; Pfeiffer, Norbert; Beutel, Manfred E.
Abstract: Objectives: The Tower of London (TOL) test has probably become the most often used task to assess planning ability in clinical and experimental settings. Since its implementation, efforts were made to provide a task version with adequate psychometric properties, but extensive normative data are not publicly available until now. The computerized TOL-Freiburg Version (TOL-F) was developed based on theory-grounded task analyses, and its psychometric adequacy has been repeatedly demonstrated in several studies but often with small and selective samples. Method: In the present study, we now report reliability estimates and normative data for the TOL-F stratified for age, sex, and education from a large population-representative sample collected in the Gutenberg Health Study in Mainz, Germany ( n =7703; 40–80 years). Results: The present data confirm previously reported adequate indices of reliability (>.70) of the TOL-F. We also provide normative data for the TOL-F stratified for age (5-year intervals), sex, and education (low vs . high education). Conclusions: Together, its adequate reliability and the representative age-, sex-, and education-fair normative data render the computerized TOL-F a suitable diagnostic instrument to assess planning ability. ( JINS, 2019, 25, 520–529)